Determinants Of Service Quality, Convenience And Costs On Satisfaction And Loyalty Communities In Sharia Pawnshops Cluster 1 Medan - Syahputra, Zulian; Batubara, Maryam; Ahmadi Bi Rahmani, Nur (Dinasti Publisher, 2024)
Using a quantitative methodology, this study analyzes primary data from 10 Pegadaian Syariah AR Hakim Medan customers via questionnaires. Sampling methodology is the method that is used. Subsequently, route analysis and SPSS Version 25 software were used to process and evaluate the gathered data. Tests for instrument validity and reliability, statistical tests (determination test, partial test (t-test), and simultaneous test (f-test), and testing for classical assumptions (data normality, multicollinearity, and heteroscedasticity) were all included in the study. The findings of the study indicate that although mun'ah fees do not significantly affect customer happiness, service quality and convenience do have a beneficial impact on contentment. Customer loyalty is positively impacted by customer pleasure. The significance test findings demonstrate that mun'ah fees have no discernible impact on consumer happiness or loyalty. However, with a 95% trust level and a 5% mistake rate, service quality and convenience have a major impact on client loyalty via satisfaction.